(untitled) (Bangladesh Journal of Bioethics, 2015)
Asia is the most diverse continent in the world in terms of culture, religion, population size, finance, education, health care, academic research, general population skills, and governmental drug regulations. Each Asian country has its own unique qualities when it comes to attracting industry sponsored clinical trials. Factors that influence selecting location of a study site for a sponsored trial are mainly population size, infrastructure, education levels, and quality of health care, cost and drug regulatory platform. Conducting research in traditional countries like Pakistan adds another dimension to the problems in assuring that research conducted in an ethical manner. The indigenous layer of the cultural values makes it even more difficult task, but this is the task that we are morally and ethically bound to shoulder.